KEEFEKTIFAN TEAM TEACHING PENDIDIK PROGRAM PENDIDIKAN DAN PENGEMBANGAN ANAK USIA DINI (PPAUD) DI KABUPATEN KULON PROGO - Benny Erifiani; Puji Yanti Fauziah (Departement of Nonformal Education, Graduate Scholl of Universitas Negeri Yogyakarta, 2014)
Penelitian ini bertujuan untuk mengetahui keefektifan: (1) Pemahaman, perencanaan, pelaksanaan, dan evaluasi pendidik program PPAUD tentang team teaching (2) hasil team teaching, dan (3) faktor pendukung dan penghambat keefektifan team teaching. Penelitian ini merupakan penelitian evaluasi dengan logic models menggunakan pendekatan kualitatif dan kuantitatif. Subjek penelitian 65 orang pendidik. Instrumen pengumpulan data yang digunakan adalah kuesioner, lembar observasi, dan pedoman wawancara. Teknik pengumpulan data yang digunakan adalah studi dokumen, wawancara, observasi dan kuesioner. Data dianalisis secara deskriptif. Hasil penelitian menunjukkan bahwa pemahaman, perencanaan, pelaksanaan, dan evaluasi team teaching efektif. Team teaching memberikan hasil positif terhadap anak, dan terdapat faktor pendukung team teaching meliputi: rasio peserta didik dan pendidik, ketersediaan sarana prasarana, rekan pendidik yang terbuka dan mempunyai keinginan kerja sama, ketercapaian tumbuh kembang anak, proses administrasi mudah dan lengkap serta bertambahnya kemampuan pendidik. Faktor penghambat meliputi: jumlah pendidik sedikit dan fasilitas sarana prasarana terbatas.Kata Kunci: keefektifan, team teaching, PAUDTHE EFFECTIVENESS OF TEAM TEACHING OF EARLY CHILDHOOD EDUCATION PROGRAM EDUCATORS IN KULONPROGO REGENCYAbstractThis study aims to investigate: (1) the effectiveness of: the educators’ understanding of team teaching, the educators’ planning in team teaching, the implementation of team teaching, and the evaluation of team teaching; (2) the result of team teaching; and (3) supporting and inhibiting factors of team teaching in Early Childhood Education Program educators in Kulon Progo Regency. This study was an evaluation study using quantitative and qualitative approaches. The evaluation model used was the logic models. The research subject were 80 educator’s with 65 educators Data were collected by means of questionnaires, observation, and interview. The technique of data analysis used was descriptive. The results show that: (1) the educators’ understanding of team teaching is quite effective with a score of 1.52 or 89%, (2) the educators’ planning in team teaching is very effective with a score of 2.79 or 93%, (3) the implementation of team teaching is very effective with a score of2.91 or 97.1%, (4) the evaluation of team teaching tremendously effective with a gained score of 2.28 or 99.3%, (5) the team teaching gives a positive effect to the children according to administrators’ and parents’ point of view, (6) the supporting factors of team teaching are: (a) the educator and children ratio, (b) the availability of infrastructure and facilities, (c) open minded and good willing to cooperate of educators’ partner, (d) the best possibility of children development, (e) the convenient and comprehensive administration process, and (f) the increase of educator’s competencies by interaction and team teaching. The inhibiting factors of team teaching are: (a). the limitation of the number of educators, and (b) the limitation of infrastructure and facilities.Keywords: effectiveness, team teaching, early childhood education